Development of wearable supercapacitor devices based on graphene and carbon nanotubes - Tong, Chii Shin. (2013)
For the purpose to improve the electrochemical performance and develop a prototype of wearable supercapacitor, a new architecture structure of wearable electrochemical electrode cell had been studied. The structure had been designed as alternating layer of P3-type single-walled carbon nanotubes and transition metal oxide (ruthenium oxide and manganese oxide) coating on a glass-fiber felt. Both electrode cells have been tested with cyclic voltammetric and impedance testing. The P3-CNTs/RuO2 has the maximum specific capacitance of 122 Fg-1 and maximum areal capacitance of 0.09 Fcm-2 in 1M H2SO4 electrolyte at scan rate of 5mVs-1. The P3-CNTs/MnO2 has the maximum specific capacitance of 106 Fg-1 and maximum areal capacitance of 0.08 Fcm-2 in 1M Na2SO4 electrolyte at 5mVs-1. Both electrode cells performance have been discussed and compared. A prototype of asymmetric wearable supercapacitor which using the P3-CNTs/RuO2 as working electrode had been fabricated.